Conceptualization of Autism in the Latino Community and its Relationship with Early Diagnosis - Zuckerman, Katharine E. (2014)
OBJECTIVE: Early identification of autism spectrum disorders (ASD) has been linked to improved long-term developmental outcomes. However, Latino children are diagnosed later than white non-Latino children. We aimed to qualitatively assess the understanding and conceptualization of ASD in the Latino community in order to understand potential community barriers to early diagnosis. METHOD: We conducted 5 focus groups and 4 qualitative interviews with 30 parents of typically-developing Latino children in Oregon. Participants were asked structured questions concerning video vignettes that follow a Latina mother from the time she begins to worry about her 3-year-old son's behaviors to the time he receives an ASD diagnosis. Focus groups and interviews were audio-recorded, transcribed and independently coded. Coded data were analyzed using thematic analysis. RESULTS: Many Latino families in the study had not heard of ASD or had little information about it. Families sometimes assumed ASD red flags were normal or could be attributed to family dysfunction. Families also had concerns about provider communication and access to language services. Having a child with a developmental delay was associated with embarrassment, rejection, and family burden, making it difficult for parents to raise developmental concerns with providers. CONCLUSION: Pediatric providers should not assume that Latino parents have heard of ASD or know its symptoms. Providers should be aware that parents may be reluctant to mention concerns due to cultural factors. The health care system needs to improve resources for Latino parents with limited English proficiency. Policies should encourage the use of developmental screening in primary care.